2017
DOI: 10.5751/ace-01086-120220
|View full text |Cite
|
Sign up to set email alerts
|

Postbreeding dispersal and staging of Common and Arctic Terns throughout the western North Atlantic

Abstract: ABSTRACT. In the western North Atlantic, Common (Sterna hirundo) and Arctic (S. paradisaea) Terns are sympatric at breeding colonies but show divergent migration strategies to coastal areas of South America and pelagic regions of the Antarctic, respectively. During 2013, we studied postbreeding movements of adult Common (n = 130) and Arctic (n = 52) Terns from four breeding colonies in the eastern USA and Canada using digital very high frequency (VHF) transmitters and an array of 62 automated radio telemetry t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 27 publications
(31 reference statements)
3
3
0
Order By: Relevance
“…Terns from our study site on average departed from Svalbard on 3 September, which is from 1 to 2 mo later than previously shown in studies from more southerly breeding areas (Table S1; Egevang et al 2010, Fijn et al 2013, Loring et al 2017, Volkov et al 2017, Alerstam et al 2019, Redfern & Bevan 2020a. The late departure date of our tracked individuals corresponds with later departure of other species from northern latitudes (Butler et al 1998, Gilg et al 2013, Davis et al 2016.…”
Section: Migration Non-breeding Areas and Population Comparisonsupporting
confidence: 61%
See 2 more Smart Citations
“…Terns from our study site on average departed from Svalbard on 3 September, which is from 1 to 2 mo later than previously shown in studies from more southerly breeding areas (Table S1; Egevang et al 2010, Fijn et al 2013, Loring et al 2017, Volkov et al 2017, Alerstam et al 2019, Redfern & Bevan 2020a. The late departure date of our tracked individuals corresponds with later departure of other species from northern latitudes (Butler et al 1998, Gilg et al 2013, Davis et al 2016.…”
Section: Migration Non-breeding Areas and Population Comparisonsupporting
confidence: 61%
“…According to Bourne & Casement (1996), Arctic terns are present in the area from late April until late October, with a distinct peak in August. This time window corresponds with breeding site departure dates of terns from lower (Egevang et al 2010, Fijn et al 2013, Loring et al 2017, Volkov et al 2017 and higher latitudes (our study; Box 1).…”
Section: Migration Patterns and The Environmentsupporting
confidence: 57%
See 1 more Smart Citation
“…This indicates that regardless of where they came from, hatch-year Roseate Terns tended to depart the Cape Cod staging grounds (permanently) around the same time, and this was similar across both years of our study. Additionally, our results for timing of departure are consistent with previous findings for Common Terns at the Cape Cod staging grounds (Nisbet et al 2011, Loring et al 2017). Together, these results suggest that some exogenous force, such as environmental conditions, day length, and so forth, may mediate the timing of tern migration in this area.…”
Section: Discussionsupporting
confidence: 92%
“…Birds from the northern region may move south to the Cape Cod area sooner and in higher numbers than birds from the southern region because of the reduction in availability of ephemeral food resources in the cold-water northern sites. Loring et al (2017) also found that Common Tern departure from the northern region (Nova Scotia colony sites) was significantly earlier than departure from Monomoy Island, a colony site in the southern region. Bird migration routes and phenology have evolved to occur concurrently with peak periods of resource availability (Stenseth and Mysterud 2002); thus, Roseate and Common Terns from the northern part of the NWA range may become food limited earlier than those from the southern region and therefore spend more time staging at Cape Cod National Seashore than their southern counterparts.…”
Section: Discussionmentioning
confidence: 79%